PERCEPTION OF THE SPORTSCASTER WITH TRAINING IN PHYSICAL EDUCATION: THE IMPORTANCE OF THEIR INITIAL FORMATION (Fiep Bulletin - online, 2014)
The present paper had as an aim to identify the perception of the sportscaster with training in Physical Education on the importance of their initial formation. The participants in the study were two professionals with training in Physical Education and who work in sports radio journalism. The data collection instrument was a semi-structured interview with 18 open questions related to the objectives of the present paper. From the results obtained it was evidenced that there's a professional connection in terms of subjects between Physical Education and Social Communication. The professionals interviewed were unanimous as for the importance of having Physical Education as a basis formation for the accomplishing of their work in sports radio journalism. Finally, it's concluded that the Physical Education professional, with their knowledge linked to the subjects, should take part in work connected with the sports context, since it's been proved that sports radio journalism counting on Physical Education professionals, will be contributing to a better qualification regarding their objectives.
Keywords: Physical Education; Sports Radio Journalism; initial formation